Bakti Sosial Jantung Sehat: Pengembangan Upaya Preventif Kardiovaskuler dan Peningkatan Kualitas Hidup Lansia - Yanna Indrayana; Herpan Syafii Harahap; Dion Setiawan; Amanda Halimi (Universitas Mataram, 2020)
Cardiovascular disease is the major causes of death in the world. Hypertension and diabetes mellitus are the important risk factors for cardiovascular disease. The prevalence of hypertension and diabetes mellitus is higher in the elderly population. Promotive and preventive efforts for the occurrence of hypertension and diabetes mellitus are the important strategies for preventing cardiovascular disease in elderly population. This was a social activity program developingthe preventive strategy against cardiovascular disease and improving of the quality of life of the elderly. This activity program was attended by 66 elderly participants routinely participated in the Panti Sosial Tresna Werdha Puspa Karma, Mataram. This program were consisted of counseling and healthy heart gymnasticsregularly every week for 3 months. The parameters taken in this event are height, body mass index (BMI), abdominal circumference, systolic and diastolic blood pressure, and serum fasting blood glucose (GDP) levels at the beginning and end of the programin order to assess the success of this program in reducingthe risk of suffered from cardiovascular disease. There were significant differences in the mean of body weight, BMI, abdominal circumference, systolic and diastolic blood pressure, and serum GDP levels between the the beginning and end of the programs (p<0.05). This social activity program reduced effectively the risk of cardiovascular disease in the elderly.